Spirits and animism in contemporary Japan: the invisible empire - Rambelli, Fabio (Bloomsbury Academic, 2019)
"This book draws attention to a striking aspect of contemporary Japanese culture: the pervasive nature of discussions and representations of "spirits" (tama or tamashii). Ancestor cults have played a central role in Japanese culture and religion for many centuries; in recent decades, however, other phenomena have contributed to expand and diversify the realm of Japanese animism. For example, many manga, anime, TV shows, literature, and art works deal with spirits, ghosts, and more in general, with an invisible dimension of reality. International contributors ask whether these are manifestations of "traditional," ancestral spirituality in their adaptations to contemporary society, or forms of commercial merchandise created by the media for consumption. Spirits and Animism in Contemporary Japan takes seriously not only the modes of representations and their possible cultural meanings of spirits, but also and especially the metaphysical implications of contemporary Japanese ideas about spirits. The chapters offer analyses of specific cases of "animistic attitudes" in which the presence of "spirits" and spiritual forces is alleged, and attempt to trace cultural genealogies of those attitudes. In particular, they present various modes of representation of spirits (in contemporary art, architecture, visual culture, cinema, literature, diffuse spirituality) while at the same time addressing their underlying intellectual and religious assumptions"--